A comprehensive literature review of conventional and modern islanding detection methods - Nauman Ali Larik; Muhammad Faizan Tahir; Z.M. Salem Elbarbary; Muhammad Zain Yousaf; Muhammad Ahmad Khan (Energy Strategy Reviews, 2022)
Distributed Energy Resources (DER) offer significant advantages by means of raising reliability of distribution system, providing clean source of electricity and reduction in fossil fuel consumption. However, penetration of DER in distribution system poses severe challenges for control procedures and maintain protection coordination for secure operation. Unintentional islanding is a threat to the safety of equipment and line worker. Different islanding detection approaches are broadly classified in remote type methods which employ communication infrastructure and local type techniques based on monitoring parameters at Distributed Generator (DG) side. In this paper broad assessment about Islanding Detection Methods (IDMs) with their limitations and benefits are explained with respect to accuracy, detection time and non-detection zone. Comparative assessments of different IDMs are listed in tabulation for conveniently judging the most economical and efficient approach.